The profile of Black South African men diagnosed with prostate cancer in the Free State, South Africa - Matthew O.A. Benedict; Wilhelm J. Steinberg; Frederik M. Claassen; Nathaniel Mofolo (South African Family Practice)
Background: Prostate cancer (PCa) ranks high in terms of morbidity and mortality, especially in Africa. Prostate-specific antigen (PSA) screening remains a practical method of screening for and thereby detecting PCa early, especially among African men who are more negatively affected. Modifiable risk factors for PCa are mostly behavioural and lifestyle. Understanding community-specific determinants is important when developing health promotion interventions.